In vitro gastrointestinal digestion of a peanut, soybean, guava and beet beverage supplemented with Lactobacillus rhamnosus GG. (August 2020) - Montanari, Shimeny Ramos; Ricardo de Castro Leite Júnior, Bruno; Martins, Maurilio Lopes; Ramos, Afonso Mota; Binoti, Mirella Lima; Cristina de Almeida Bianchini Campos, Renata; Narvaes da Rocha Campos, André; Furtado Martins, Eliane Maurício
Abstract: The resistance of Lactobacillus rhamnosus GG (LGG) to in vitro gastrointestinal digestion in mixed beverages (MB) prepared with legumes, peanut (MBPP) or soybean (MBSP), containing guava pulp and beet was evaluated, as well as the physical-chemical, microbiological and sensorial characteristics of these products. For this purpose, 4 beverages (MBPP and MBSP with probiotic and MBPC and MBSC as a control, without probiotic) were prepared. MBPP and MBSP was fermented and maintained together with their controls at 8 °C for 42 days. In the in vitro test of gastrointestinal resistance, for 100 mL of beverage 8.34 and 7.50 Log CFU/mL of LGG were available after digestion in BMPP and BMSP, respectively, which makes these products potential probiotics. The viability of LGG was >7.3 Log CFU/mL throughout storage in the beverages, which were microbiologically safe for consumption. The beverages containing LGG showed higher acidity and lower pH after processing compared to those without fermentation. Soybean beverages showed higher protein content (p < 0.05) compared to peanut beverages, which did, however, have higher lipids. After processing, the products showed hedonic scores equivalent to "I liked it a little" and "I liked it a lot", which suggested a willingness to consume the product, thus possibly being viable non-dairy beverages. Graphical abstract: Image 1 Highlights: A soybean, peanut, guava and beet mix may be a good carrier of Lactobacillus rhamnosus . Viability and resistance to the in vitro gastrointestinal digestion were determined. Formulations were sensorially acceptable with good functionality. The product may be a possible non-dairy beverage.